Industrial policy in the EU and its neighbourhood: learning from policy experimentation - Benner, Maximilian (Economies, 2019)
Newer approaches of industrial policy that focus on catalytic and facilitating interventions of government have become a rivalling model to neoclassical laissez-faire approaches. Inspired by the success stories of East Asian newly industrialised economies (NIEs), newer approaches advocate a more experimental policy stance. Newer industrial policies, including the concept of the "entrepreneurial state", call upon governments to play a catalytic and facilitating role in increasing innovation and, thus, economic growth. During the past three decades, countries have experimented with some of these new approaches, and so has the European Union (EU). Currently, two major policy frameworks of the EU, Horizon 2020 and smart specialisation, shape the European approach to industrial policy and are gaining in importance for enlargement and neighbourhood countries, too. At the same time, these countries outside the EU have pursued their own experiments in industrial policy. The article argues that to better understand what contributes to the success or failure of industrial policies, learning from experiences made both by the EU and its neighbours is valuable. The article draws conclusions from three countries in the EU's neighbourhood, Israel, Tunisia, and North Macedonia. In particular, the article examines the role EU approaches and programs, such as smart specialisation or Horizon 2020, can play in anchoring more entrepreneurial industrial policies in enlargement and neighbourhood countries and addresses problems to be expected when governments are to engage in policy experimentation.